The Analysis of Idiomatic Expression in Selected Backstreet Boys' Songs - Anggy Pratiwi; Yenita Uswar; Yuri Chalista; Kezia Artieva Lubis; Suan Marcello Harianja (ITScience (Information Technology and Science), 2026)
Every language has literal and figurative meanings. Literal meaning is the direct reference of words or sentences to objects, while figurative meaning is used to give an imaginative description or a special effect, just like idioms. This research aims to identify the idiomatic expressions used in selected Backstreet Boys’ songs and the categories to which they belong. This research employed a qualitative approach focused on content or document analysis. The method used in this research is descriptive qualitative, used to analyze and categorize the idiomatic expressions found in those songs. The procedures used in analyzing the data were preparation, reading, coding, description, and interpretation. The researchers browsed the songs, sought its lyrics, listened to it, and transcribed it. Subsequently, the data analysis involved reading, analyzing, identifying, and classifying the types of idiomatic expressions in the song’s lyrics and finally concluding. After analyzing the data, the researchers found that six idiomatic expressions depicted in the lyrics were based on the theory of O’Dell & McCarty (2010), which were binomials, cliches, proverbs, euphemisms, and similes. and Fernando’s theory (1996), which was pure idioms. The dominant idiomatic expression that the researchers found they were 51. 56% pure idioms, followed by proverbs at 18.75%. The dominance of pure idioms and proverbs in the selected Backstreet Boys’ songs comes down to a deliberate mix of commercial pop songwriting strategy, emotional songwriting choices, and a unique linguistic quirk involving their Swedish producers Keywords— Literal and figurative Meaning, Idiomatic Expression, Backstreet Boys’ Songs.